2022
DOI: 10.1002/admt.202200238
|View full text |Cite
|
Sign up to set email alerts
|

Engineering MOFs‐Derived Nanoarchitectures with Efficient Polysulfides Catalytic Sites for Advanced Li–S Batteries

Abstract: Owing to the dramatic growth in energy expending and the inevitable greenhouse effect, [1] it is a significant challenge to exploit new energy-storage technologies with extraordinary energy density and good sustainability. During the last decades, Li-ion batteries have played an imperative character in meeting the growing demands of electronic devices. However, as a rechargeable storage device, the Li-ion batteries have also faced many limitations because of their relatively low capacity and insufficient energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 305 publications
0
4
0
Order By: Relevance
“…The CoSAC@CNTs present a notable surface area (S BET ) of 920.15 m 2 g −1 , surpassing the reported values of other Co-containing catalysts from previous studies. 58,59 As per computations based on the density functional theory (DFT) methodology, the material has an average pore size of 9.7 nm and an overall pore volume of 1.4 cm 3 g −1 . The process of pyrolysis plays a role in controlling the specific surface area and porosity of substances.…”
Section: Resultsmentioning
confidence: 99%
“…The CoSAC@CNTs present a notable surface area (S BET ) of 920.15 m 2 g −1 , surpassing the reported values of other Co-containing catalysts from previous studies. 58,59 As per computations based on the density functional theory (DFT) methodology, the material has an average pore size of 9.7 nm and an overall pore volume of 1.4 cm 3 g −1 . The process of pyrolysis plays a role in controlling the specific surface area and porosity of substances.…”
Section: Resultsmentioning
confidence: 99%
“…Pristine MOFs used as electrodes in batteries have been mainly restricted by their stability issues, low capacity, poor conductivity, and weak adhesion to the substrate. On the other hand, functional MOF derivatives such as metal sulfides, metal phosphide, metal oxides, and nanometals embedded in porous carbons are generally more efficient for rechargeable batteries. The unique structural features of MOFs and their ability to coordinate different metal ions in their secondary building units as in the case of multivariate-MOFs (MTV-MOFs), makes MOFs uniquely suited for advancing the design and performance of electrocatalytic electrodes . This top-down approach enables rapid cathode fabrication and eliminates several challenges encountered with traditional methods like wet chemical methods of coprecipitation and impregnation or gas phase processes, including chemical vapor deposition and atomic layer deposition that suffer from metal nanoparticle agglomeration or the need for advanced fabrication tools. , To this end, we envisioned that thermolysis of MTV-MOFs of selected metal composition under controlled reaction conditions could lead to superior sulfur cathodes that combine a high LiPS anchoring ability and rapid redox kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above modification strategies, inorganic catalysts have been widely applied to overcome intrinsic shortcomings of BiVO 4 . On this occasion, novel molecular catalysts and metal-organic framework co-catalysts, including Co-based POM (polyoxometalate), [29] porphyrin derivatives, [30] NiFe-MOFs and MIL-101, [31][32][33][34][35] and COFs, [36] have been considered as the most promising materials owing to their high catalytic activity and easy preparation.In simulation of the conversion process between solar energy and electron in photosynthesis, it is found that semiconductors in the photoelectrochemical reaction are equivalent to the role of chlorophyll to absorb sunlight through the charge transfer process, which can break the OH bond to achieve water splitting. In this case, it is found that porphyrins and phthalocyanines have similar structures to that of photosensitive chlorophyll in nature, [30,37] which are usually used as photocatalysts to increase the efficiency of photo-generated holes reaching the surface of catalyst.…”
mentioning
confidence: 99%
“…Based on the above modification strategies, inorganic catalysts have been widely applied to overcome intrinsic shortcomings of BiVO 4 . On this occasion, novel molecular catalysts and metal-organic framework co-catalysts, including Co-based POM (polyoxometalate), [29] porphyrin derivatives, [30] NiFe-MOFs and MIL-101, [31][32][33][34][35] and COFs, [36] have been considered as the most promising materials owing to their high catalytic activity and easy preparation.…”
mentioning
confidence: 99%